Akulturasi Adat dan Islam dalam Tradisi Masyarakat Desa Lamahala Jaya: Perspektif Pendidikan dan Keagamaan - aliumar, ali (Balai Diklat Keagamaan Denpasar, 2025)
This study aims to discuss the process of acculturation between customs and Islam in Lamahala Jaya Village, East Adonara District, East Flores Regency from an educational and religious perspective. This acculturation occurs in various aspects of social, religious, and educational life, creating harmony between traditional values ​​and Islamic teachings. Using a descriptive qualitative approach, this study reveals that local traditions are maintained with adjustments to be in harmony with Islamic teachings. Traditional ceremonies, commemorations of Islamic holidays, and customary deliberations are real examples of how Islam and local culture can blend without causing clashes of values. However, modernization and globalization present challenges to the sustainability of this acculturation, especially in the inheritance of values ​​to the younger generation. Therefore, a revitalization strategy through education based on customs and Islam is needed to maintain a balance between cultural heritage and religious teachings. The results of this study indicate that the acculturation of customs and Islam not only maintains cultural identity, but also strengthens Islamic values ​​in the lives of the local community.